THE INFLUENCE OF PRICE VALUE AND KNOWLEDGE TRANSMISSION ON INTENTION TO ADOPT ROOFTOP PV SYSTEMS IN RESIDENTIAL - Putri Yasmin Herdianti; Abdul Malik Sayuti (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
PURPOSE - The energy transition is a key priority in achieving Indonesia’s net zero emission target, with rooftop photovoltaic (PV) systems promoted as a solution. However, adoption in residential areas, especially in Bandung Raya, remains low. This study investigates the influence of price value and knowledge transmission on intention to adopt rooftop photovoltaic (PV) systems in residential of Bandung Raya.METHODOLOGY - . A quantitative approach was employed, with data gathered through an online survey Google Form, resulting in 253 valid responses.FINDING - The findings indicate that both price value and knowledge transmission have a significant combined influence on adoption intention, with a determination coefficient (R²) of 0.648. These insights are expected to support the development of public policies and marketing strategies by energy sector stakeholders, particularly by emphasizing educational outreach and affordable pricing options to promote greater household adoption of rooftop PV systems.